The Relationship Between Fear-Avoidance and Objective Biomechanical Measures of Function in Patients With Adult Degenerative Scoliosis. Issue 9 (1st May 2018) - Haddas, Ram; Lieberman, Isador H.; Block, Andrew
Abstract : Study Design: A prospective cohort study. Objective: The current study utilized quantitative gait analysis to examine the relationship of fear-avoidance beliefs to gait patterns in patients with adult degenerative scoliosis (ADS). Summary of Background Data: Among patients with chronic spine pain, fear-avoidance beliefs are predictive of behavioral deficiencies, poor work, and surgery outcomes. The impact of such beliefs on patients with major spinal deformity has yet to be investigated. Patients with ADS have previously been shown to have an altered gait pattern. Utilizing quantified gait analysis, this study aims to examine correlations between fear-avoidance and various aspects of gait in patients with ADS. Methods: Twenty-five ADS patients completed the Tampa Scale for Kinesiophobia (TSK) questionnaire and the Fear Avoidance Beliefs Questionnaire (FABQ). Each patient performed a series of overground gait trials at a self-selected comfortable speed. Pearson product correlation analysis was used to determine the relationship between the self-reported fear of movement measures and the objective gait analysis biomechanical data. Results: TSK score correlated strongly with gait speed, stride, step, double support times, and step length, and correlated moderately with cadence, and stride length. The FABQ physical portion strongly correlated with stride length and step length. The FABQ physical portion was moderately correlated with gait speed and single support time. The FABQ work portion was correlated with stride length and step length. Conclusion: This study demonstrates a strong correlation between biomechanical gait parameters, as measured with gait analysis, and fear-avoidance of movement, as measured with the TSK and FABQ. Further, it demonstrates that quantified gait analysis can be a useful tool to evaluate patients with spine deformity and to assess the outcomes of treatments in this group of patients. This study extends previous research on the role of fear-avoidance to include patients with spinal deformity. Level of Evidence: 3